PENGAWASAN DINAS PERDAGANGAN DAN PERINDUSTRIAN KOTA PEKANBARU TERHADAP TIMBANGAN PEDAGANG DI PASAR TRADISIONAL KOTA PEKANBARU MELALUI PELAKSANAAN TERA ULANG TAHUN 2018 - Putri, Novi Vin Dwi; ", Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Writing a thesis entitled " Supervision Of The Pekanbaru City Trade And Industry Service On The Scales Of Traders In Pekanbaru City Traditional Markets Through The Implementation Of Tera In 2018". There are factors ineffective service supervision of traders' scales and traders who still use scales that have not been calibrated or the scales are canceled, namely from internal factors and external factors. This research was conducted at the Trade and Industry Office of Pekanbaru City, the trade and industry section of the metrology supervisory section. The purpose of this research is to describe the Supervision Of The Pekanbaru City Trade And Industry Service On The Scales Of Traders In Pekanbaru City Traditional Markets Through The Implementation Of Tera In 2018. The theory used is Bohari's theory of Preventive Supervision and Repressive Supervision. The research method used by the author is descriptive qualitative with interview data collection techniques and documentation. The type of data used by the author is primary data and secondary data. The results of this study are to determine the supervision carried out by the trade and industry office of Pekanbaru City in the field of trade and industry in the Metrology Supervisory Section in supervising traders' scales in traditional markets in Pekanbaru City, and so far the supervision of the Trade and Industry office has not been effective. Key words: supervision, scales, traders